2018
DOI: 10.1111/flan.12352
|View full text |Cite
|
Sign up to set email alerts
|

Striving for the third space: A U.S. professional's experiences in Chinese workplaces

Abstract: This single‐case study explored the experiences of a U.S. professional working in China by focusing on his discursive performance in negotiating a third space at work with people from the target culture. The results revealed that the foreign professional demonstrated a strong desire to creatively appropriate the target language as his own use, which went hand‐in‐hand with his advanced language skills and cultural knowledge, allowing him to assume full responsibility for his own linguistic choice. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Such challenges may be intensified with Westerners, in particular, as they strongly value leadership, initiative, and candor. In his case study of a U.S. student working in China after his graduation, Zeng (2018) observed that although the student demonstrated advanced proficiency in Chinese, his attempt to change conventional Chinese expressions creatively and playfully yet understandably by his Chinese counterparts was often nicely praised as "foreign flavor" (p.671) and received with an expectation of him to conform to communicative conventions that reflected Chinese counterparts' "deep adherence to Chinese cultural values" (p. 671).…”
Section: Discrepancy Around Intercultural Conflict Managementmentioning
confidence: 99%
“…Such challenges may be intensified with Westerners, in particular, as they strongly value leadership, initiative, and candor. In his case study of a U.S. student working in China after his graduation, Zeng (2018) observed that although the student demonstrated advanced proficiency in Chinese, his attempt to change conventional Chinese expressions creatively and playfully yet understandably by his Chinese counterparts was often nicely praised as "foreign flavor" (p.671) and received with an expectation of him to conform to communicative conventions that reflected Chinese counterparts' "deep adherence to Chinese cultural values" (p. 671).…”
Section: Discrepancy Around Intercultural Conflict Managementmentioning
confidence: 99%
“…247–248, italics added). Emotional engagement and intensive relationships emerged in a broad array of settings, including homestays, but also shared lodging, workplaces, recreational affinity spaces (see also, e.g., Fukada, ; Gaugler and Matheus, ; Kinginger & Wu, ; Zeng, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…These students are advanced-level Chinese language learners who expect to bring their Chinese proficiency to an even higher level and gain the ability to demonstrate expertise in their chosen domains. Although the definition and description of advanced-level language proficiency has been well discussed, relatively little has been explored about advanced-level Chinese learners' nonlinguistic variables including their overall domain expertise (McAloon, 2015;Zeng, 2018). Zeng in her recent work states the importance of helping advanced-level language learners to develop their domain specific knowledge and language use in multicultural contexts (Zeng, 2018, p. 675).…”
Section: Curriculum Shiftmentioning
confidence: 99%